Engaging a rural community in identifying determinants of low birth weight and deciding on measures to improve low birth weight: an experience from a Sri Lankan study - N. D. Galmangoda Guruge; M. Goonasekara; S. D. Dharmaratne; M. W. Gunathunga (BMC, 2017)
Abstract Background Involving communities in identifying and addressing determinants of their own health is effective in addressing complex problems, such as low birth weight (LBW). LBW is an important public health problem which has not improved significantly in Sri Lanka in the last 10 years. This study reports the ability of lay persons to identify and address determinants of LBW. Methods A health promotion intervention was conducted among 403 mothers registering at 26 antenatal clinics in the district of Anuradhapura, in Sri Lanka. The components of a health promotion process-initiation, maintenance and continual monitoring, and re-direction towards greater effectiveness-were explained to the mothers. Inputs were initially provided through different methods to enable mothers' groups to identify determinants of LBW and to decide actions to address those identified determinants. The overall study was carried out over a period of 1 year, of which the intervention phase took around 7 months. The mothers in the clinic group were encouraged to continue an ongoing process in smaller "neighborhood action committees" (NACs)-of which there were 71. The findings are based on field notes maintained during the process, analyzed using thematic analysis. Results Each group of mothers identified at least eight determinants of LBW at the first attempt (without first author's guidance), four of which corresponded with those already mentioned in published studies. Up to five other determinants were agreed, after facilitation by the first author, at the second attempt. Of the total, 10 determinants of LBW were finally prioritized. Twenty actions to address the 10 selected prioritized determinants were agreed through a collective consensus development process. Conclusions Lay communities successfully identified determinants of LBW and household level actions to address these, with relatively simple guidance, when stimulated to initiate the relevant process. This capacity should be nurtured and better used in interventions to improve LBW.